2009
DOI: 10.1002/0471140864.ps1110s57
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminal Sequence Analysis of Proteins and Peptides

Abstract: Automated N-terminal sequence analysis involves a series of chemical reactions that derivatize and remove one amino acid at a time from the N-terminus of purified peptides or intact proteins. At least several picomoles of a purified protein or 10 to 20 pmol of a purified peptide with an unmodified N-terminus is required to obtain useful sequence information. In recent years, the demand for N-terminal sequencing has decreased substantially as some applications for protein identification and characterization can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…N-terminal sequencing of NVCP, sucrose gradient centrifugation and electron microscopy for NVCP VLP, and GFP visualization were all performed according to published protocols (Huang, et al 2009; Santi, et al 2008; Speicher, et al 2001). …”
Section: Methodsmentioning
confidence: 99%
“…N-terminal sequencing of NVCP, sucrose gradient centrifugation and electron microscopy for NVCP VLP, and GFP visualization were all performed according to published protocols (Huang, et al 2009; Santi, et al 2008; Speicher, et al 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the identified disulfide‐linked peptides are characterized by MS (see Current Protocols article: Zhang, Annan, Carr, & Neubert, , for overview). N‐terminal Edman sequencing (Speicher, Gorman, & Speicher, ) is an older method that was traditionally used to obtain sequence information of reduced peptides. However, this method has largely been replaced by tandem MS (see Current Protocols article: Moore, Young, & Lee, ).…”
Section: Strategic Planningmentioning
confidence: 99%
“…The partial reduction and alkylation strategy was used to determine the three disulfide linkages of the T2 complex. The alkylated cysteine residues are indicated by the italicized lowercase "c." MALDI-MS (Sandoval, 2014) and Edman sequencing (Speicher et al, 2009) of the T2-R3 and T2-R5 complexes revealed disulfide-bond formation between Cys6-Cys36, and between Cys15-Cys25, respectively. Based on the two disulfide bond assignments, the third disulfide bond is deduced to form between resulting in disulfide-cleaved peptides that are further fragmented using CID or HCD for sequence information (Liu, van Breukelen, & Heck, 2014;Ni et al, 2013;Wang, Lu, Wu, Karger, & Hancock, 2011).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Identification of the N terminal sequence of an intact or cleaved protein is crucial for its biochemical and structural characterization [1]. In conventional shotgun proteomic analysis, it is difficult to identify protein N-termini due to infrequent detection of protein N-terminal peptides.…”
Section: Introductionmentioning
confidence: 99%